The rapid growth phase of supermassive black holes. Issue 3 (11th September 2018) - McAlpine, Stuart; Bower, Richard G; Rosario, David J; Crain, Robert A; Schaye, Joop; Theuns, Tom
ABSTRACT: We investigate the rapid growth phase of supermassive black holes (BHs) within the hydrodynamical cosmological eagle simulation. This non-linear phase of BH growth occurs within ∼ L * galaxies, embedded between two regulatory states of the galaxy host: in sub L * galaxies efficient stellar feedback regulates the gas inflow on to the galaxy and significantly reduces the growth of the central BH, while in galaxies more massive than L * efficient AGN feedback regulates the gas inflow on to the galaxy and curbs further non-linear BH growth. We find evolving critical galaxy and halo mass scales at which rapid BH growth begins. Galaxies in the low-redshift Universe transition into the rapid BH growth phase in haloes that are approximately an order of magnitude more massive than their high-redshift counterparts ( M 200 ≈10 12.4 M⊙ at z ≈ 0 decreasing to M 200 ≈10 11.2 M⊙ at z ≈ 6). Instead, BHs enter the rapid growth phase at a fixed critical halo virial temperature ( T vir ≈ 10 5.6 K). We additionally show that major galaxy–galaxy interactions (μ 14, where μ is the stellar mass ratio) play a substantial role in triggering the rapid growth phase of BHs in the low-redshift Universe, whilst potentially having a lower influence at high redshift. Approximately 40 per cent of BHs that initiate the rapid BH growth phase at z ≈ 0 do so within ±0.5 dynamical times of a major galaxy–galaxy merger, a fourfold increase above what is expected from the background merger rate. We find that minor mergers (110 μ 14 ) have a substantially lower influence in triggering the rapid growth phase at all epochs.